(untitled) (Research, Society and Development, 2020)
Objective: to reflect on the contribution of experiences in university extension activities in the formation process of professionals in gerontogeriatrics and reflect on health technologies as teaching-learning strategies in extension activities with the elderly. Method: reflective study, based on conceptions about university extension and its contributions between higher education institutions and society, acting as a training space in the area of health care for the elderly. Results: the university extension shows itself as a tool positively capable of meeting all the perspectives related to critical-reflexive approaches operating among professionals in training and especially in the area of gerontology, which extends the most diverse forms of technologies to be used. Final Considerations: it seeks the modification of the formation curricula, including the health of the elderly as a fundamental discipline in the formation process, the training of the professionals acting, the wide dissemination of information related to the elderly person. As well as, the production of a structural basis to put into practice the academic activities created and executed with the elderly.